The indwelling eaudiobook Left behind series, book 7. - LaHaye, Tim (Left Behind, 1989)
With tens of millions of copies in print, the Left Behind books are the fastest-selling series of all time. Creating a thrilling scenario of the end times upon planet Earth, with the ultimate battle between good and evil being waged, the series combines Biblical prophecy with current events. It has been three and a half years since the Rapture took up the bodies of the innocent to Heaven. The prophecies foretell that this is the point when the seven-year Tribulation shall become the Great Tribulation, with the forces of evil tightening their grip on humanity in preparation for the final battle. As the world mourns the death of a renowned leader, the Tribulation Force looks for the next predicted sign - that Satan will take possession of the Antichrist and raise him from the dead! Narrator Richard Ferrone gives a rugged, suspenseful reading to this action-packed continuation of a series that includes such thrilling titles as Left Behind and Assassins.